Torso Simulation Research on Electromagnetic Compatibility of Implantable Neurostimulator - Qifei LI; Weiming WANG; Weiqiang ZHANG; Linzhi DAI; Jiawei LIU (Zhongguo yiliao qixie zazhi)
In the YY 0989.3—2023 standard, clause 27.106 specifies the protection test against electromagnetic interference, but it only briefly describes the test level for electromagnetic exposure, and does not detail the parameters of the torso. This study aims to explore the internal field distribution for different torso parameters under electromagnetic exposure, and explore the patterns of field distribution through modeling and simulation. The results indicate that the parameters of the torso significantly affect the internal field distribution. The findings of this study provide a basis and reference for the electromagnetic compatibility test for implantable neurostimulator products.